2021
DOI: 10.1017/s0007123420000599
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Relationship Between Class Position and Political Preferences: A Long-Term Panel Analysis of Intra-Generational Class Mobility

Abstract: Past findings on the connection between class position and political preferences are overwhelmingly derived from cross-sectional studies, which provided a limited basis for inferring causality. This study uses long-term panel data on thousands of British respondents to measure the impact of intra-generational class mobility across a range of political identities and preferences. Upward class mobility leads to small increases in economic conservatism, but party choice, class identity and attitudes to non-econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…More recently, a wave of studies (summarised in Margalit ( 2019)) have been published using panel data tracking individuals over time. A number find at least some evidence that preferences are updated (Ares 2020;Langsaether et al 2020;Naumann et al 2016;Owens and Pedulla 2014;Pahontu 2021). Others, however, find that any updating is only small, short-lived, or confined to certain groups, or may occur only in response to large changes in circumstances (Lerman and McCabe 2017;Margalit 2013;Marten 2019;O'Grady 2019;Stegmueller 2013;Wehl 2020).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a wave of studies (summarised in Margalit ( 2019)) have been published using panel data tracking individuals over time. A number find at least some evidence that preferences are updated (Ares 2020;Langsaether et al 2020;Naumann et al 2016;Owens and Pedulla 2014;Pahontu 2021). Others, however, find that any updating is only small, short-lived, or confined to certain groups, or may occur only in response to large changes in circumstances (Lerman and McCabe 2017;Margalit 2013;Marten 2019;O'Grady 2019;Stegmueller 2013;Wehl 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, despite the decline of the magnitude of differences between social classes, the order in which different strata favour left or right parties is still consistent with the class voting literature (Jansen, Evans, and Graaf 2013, 72). Similarly, empirical evidence shows a persistent association between social class and political preferences (Ares 2020;Langsaether 2019;Langsaether, Evans, and O'Grady 2021).…”
Section: Introductionmentioning
confidence: 95%
“…Finally, unlike sociocultural professionals, working‐class ministers might be less representative of their class than it is often assumed because they have experienced a substantial upward movement in the class hierarchy. Two recent studies that analyse the effect of class mobility on respondents’ economic preferences found that upward class mobility is associated with a modest decline in the progressivity of economic preferences (Ares, 2020; Langsæther et al., 2021). The heterogenous political preferences of the working class have also become manifest in the decline of the working‐class vote to social democratic parties.…”
Section: Social Class and Economic Preferencesmentioning
confidence: 99%
“…Second, cabinet ministers might not fully represent their social class since by the time they are appointed to the cabinet, they have spent, on average, 10 years as members of parliament. People's economic preferences become more conservative as they climb the class ladder, particularly when they move up from working class to professional occupations (Ares, 2020; Langsæther et al., 2021). In addition, these politicians are bound to be amongst the most ambitious compared with the backbenchers (Allen et al., 2020).…”
Section: Introductionmentioning
confidence: 99%